LOCAL ANAESTHETIC SYSTEMIC TOXICITY AWARENESS AMONG CLINICAL PRACTITIONERS: LAST – Critical Management - Abbas, Sana; Akram, Amjad; Abbas, Beenish; Fayyaz, Mohsin; Mehmood, Basit; Hayat, Umer (Pakistan Armed Forces Medical Journal, 2021)
Objective: to assess comprehension of local anaesthetic systemic toxicity among clinical practitioners.Study Design: Cross-sectional study.Place and Duration of Study: Tertiary Care Institute, from Dec 2019 to Mar 2020.Methodology: Methodology constituted of a web-based questionnaire. A pilot study carried out at 15-20 participants forquestionnaire validation and reviewed by independent experts for face validity, a final questionnaire comprised of 10 multiple-choice questions in addition to demographic profile.Results: A total of 950 participants participated in the study and data was extracted from their responses. Out of 738 (77.8%) participants declared that they are unaware of local anaesthetic systemic toxicity complication, 26 (2.7%) encountered local anaesthetic systemic toxicity and 185 (19.5%) never experienced. Ninety (9.5%) were aware of the availability and utilization of 'Lipid Emulsion' therapy to treat ‘Local Anaesthetic Systemic Toxicity’ (LAST).Conclusion: Although clinicians have significant awareness level regarding local anaesthetic toxicity but unfortunately compliance with management of this life-threatening complication is deficient.